The global proliferation of aquatic, benthic Microcoleus: Taxonomy, distribution, toxin production, ecology, and future directions - Laura T. Kelly; Daniel G. Beach; Joanna R. Blaszczak; Keith Bouma-Gregson; Sydney M. Brown; Haowu Cheng; Janette L. Davidson; Jutta Fastner; Marcus Francis; Andrea Garcia Jimenez; Laurel Genzoli; Ramesh Goel; et al. (Water Research, 2026)

The natural products magnetic resonance database (NP-MRD): comprehensive resource for natural products NMR data enabling discovery and understanding - John R. Cort; Jessica L. Bade; Roger G. Linington; Matthew Pin; Ella F. Poynton; Lloyd W. Sumner; James T. Koller; Zachary M. Tretter; Bharat Goel; David S. Wishart; Vasuk Gautam; Scott McKay; et al. (Phytochemistry Letters, 2025)

In-vitro Anti-inflammatory Potential of Standardized Rottlerin Enriched Fraction of Mallotus philippensis Muell. Arg Anti-inflammatory Potential of Rottlerin Enriched Fraction of Mallotus philippensis - Nancy Tripathi; Kapil Mandrah; Bharat Goel; Nivedita Bhardwaj; Vinod Kumar Paswan; G. Ravikanth; Somendu K. Roy; Shreyans K. Jain (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Extreme-aged patients (≥ 85 years) experience similar outcomes as younger geriatric patients following chronic subdural hematoma evacuation: a matched cohort study - Peyton L. Nisson; John J. Francis; Michelot Michel; Keshav Goel; Chirag G. Patil (GeroScience, 2024)
Subdural hematoma (SDH) evacuation represents one of the most frequently performed neurosurgical procedures. Several reports cite a rise in both the age and number of patient’s requiring treatment, due in part to an aging population and expanded anticoagulation use. However, limited data and conflicting conclusions exist on extreme-aged geriatric patients (≥ 85 years of age) after undergoing surgery. Patients undergoing SDH evacuation at a tertiary academic medical center between November 2013-December 2021 were retrospectively identified. The study group consisted of patients ≥ 85 years (Group 1) diagnosed with a chronic SDH surgically evacuated. A control group was created matching patients by 70–84 years of age, gender, and anticoagulation use (Group 2). Multiple metrics were evaluated between the two including length-of hospital-stay, tracheostomy/PEG placement, reoperation rate, complications, discharge location, neurological outcome at the time of discharge, and survival. A total of 130 patients were included; 65 in Group 1 and 65 in Group 2. Patient demographics, medical comorbidities, SDH characteristics, international normalized ratio, partial thromboplastin time, and use of blood thinning agents were similar between the two groups. Kaplan Meier survival analysis at one-year was 80% for Group 1 and 76% for Group 2. No significant difference was identified using the log-rank test for equality of survivor functions ( p = 0.26). All measured outcomes including GCS at time of discharge, length of stay, rate of reoperations, and neurological outcome were statistically similar between the two groups. Backwards stepwise conditional logistic regression revealed no significant association between poor outcomes at the time of discharge and age. Alternatively, anticoagulation use was found to be associated with poor outcomes (OR 3.55, 95% CI 1.08–11.60; p = 0.036). Several outcome metrics and statistical analyses were used to compare patients ≥ 85 years of age to younger geriatric patients (70–84 years) in a matched cohort study. Adjusting for age group, gender, and anticoagulation use, no significant difference was found between the two groups including neurological outcome at discharge, reoperation rate, and survival.

Reassessing the availability of crop residue as a bioenergy resource in India: A field-survey based study - Taveen S. Kapoor; Chimurkar Navinya; Gupta Anurag; Pradnya Lokhande; Shubham Rathi; Anubha Goel; Renuka Sharma; Rahul Arya; Tuhin K. Mandal; K.P. Jithin; Shiva Nagendra; Mohd Imran; et al. (Journal of Environmental Management, 2023)

Site-specific characterisation of hydrogeological parameters for low-level solid radioactive waste disposal facility at Tarapur, India - Shelly Goel; Manish Chopra; Aditi C Patra; Faby Sunny; G Ganesh; R B Oza; M S Kulkarni (Journal of Earth System Science, 2023)

Electronic nose and wireless sensor network for environmental monitoring application in pulp and paper industry: a review - Poonam Prasad; Piyush Raut; Sangita Goel; Rajesh P Barnwal; G. L. Bodhe (Environmental Monitoring and Assessment, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Insights into direct interspecies electron transfer mechanisms for acceleration of anaerobic digestion of wastes - D. Sharma; R. Mahajan; G. Goel (International Journal of Environmental Science and Technology, 2019)

Evaluating anaerobic and aerobic digestion strategies for degradation of pretreated pine needle litter - R. Mahajan; A. Nikitina; Y. Litti; A. Kallistova; A. Nozhevnikova; G. Goel (International Journal of Environmental Science and Technology, 2019)

Identification of ‘Candidatus Phytoplasma asteris’ causing sesame phyllody disease and its natural weed host in Jammu, India - A. K. Singh; Gopala; Ashutosh Rao; Sonia Goel; G. P. Rao (Indian Phytopathology, 2018)

Identification and characterization of Candidatus Phytoplasma trifolii (16SrVI-D) inducing shoot proliferation disease of potato in India - G. P. Rao; A. Mishra; M. K. Mishra; Ashutosh Rao; Sonia Goel (Indian Phytopathology, 2018)

Mortality associated with candidemia in non-neutropenic cancer patients is not less compared to a neutropenic cohort of cancer patients - G. Goel; M. Chandy; A. Bhattacharyya; S. Banerjee; S. Chatterjee; S. Mullick; S. Sinha; K. Sengupta; K. Dhar; S. Bhattacharya; S. Rudramurthy; A. Chakrabarti (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Five Critical Areas that Combat High Costs and Prolonged Development Times for Regenerative Medicine Manufacturing - Joshua G. Hunsberger; Sandeep Goel; Julie Allickson; Anthony Atala (Current Stem Cell Reports, 2017)

Development of an efficient, genotype independent plant regeneration and transformation protocol using cotyledonary nodes in safflower (Carthamus tinctorius L.) - V. Patial; R. Krishna; G. Arya; V. K. Singh; M. Agarwal; S. Goel; A. Jagannath; A. Kumar (Journal of Plant Biochemistry and Biotechnology, 2016)

Response of indigenously developed bacterial consortia in progressive degradation of polyvinyl chloride - Mohammad S Anwar; Anil Kapri; Vasvi Chaudhry; Aradhana Mishra; Mohammad W. Ansari; Yogesh Souche; Chandra S. Nautiyal; M. G. H. Zaidi; Reeta Goel (Protoplasma, 2016)

Numerical study of a buoyant plume from a multi-flue stack into a variable temperature gradient atmosphere - Ratna Kishore Velamati; M. Vivek; K. Goutham; G. R. Sreekanth; Santosh Dharmarajan; Mukesh Goel (Environmental Science and Pollution Research, 2015)

Curative effect of Terminalia chebula extract on acetic acid-induced experimental colitis: role of antioxidants, free radicals and acute inflammatory marker - M. K. Gautam; Shalini Goel; R. R. Ghatule; A. Singh; G. Nath; R. K. Goel (Inflammopharmacology, 2013)

Surface Plasmon Resonance Biosensor for Detection of Bacillus anthracis, the Causative Agent of Anthrax from Soil Samples Targeting Protective Antigen - N. Ghosh; G. Gupta; M. Boopathi; V. Pal; A. K. Singh; N. Gopalan; A. K. Goel (Indian Journal of Microbiology, 2013)

Transformation of pWWO in Rhizobium leguminosarum DPT to Engineer Toluene Degrading Ability for Rhizoremediation - Garima Goel; Piyush Pandey; Anchal Sood; Sandeep Bisht; D. K. Maheshwari; G. D. Sharma (Indian Journal of Microbiology, 2012)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Characterization of protein transacetylase from human placenta as a signaling molecule calreticulin using polyphenolic peracetates as the acetyl group donors - Seema; Ranju Kumari; Garima Gupta; Daman Saluja; Ajit Kumar; Sanjay Goel; Yogesh K. Tyagi; Ruchika Gulati; Anjali Vinocha; Kambadoor Muralidhar; Bilikere S. Dwarakanth; Ramesh C. Rastogi; et al. (Cell Biochemistry and Biophysics, 2007)

Experimental and theoretical analysis of selective hydrogenation of p-nitroanisole to p-anisidine over Pd/C: kinetics and catalyst deactivation - G. Yadav; P. Goel (Clean Technologies and Environmental Policy, 2003)

A new efficient catalyst UDCaT-1 for the alkylation of ethylbenzene with ethanol to diethylbenzene - G. Yadav; P. Goel (Clean Technologies and Environmental Policy, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Evaluation of effectiveness of a facet wiring technique: Anin vitro biomechanical investigation - Vijay K. Goel; Charles R. Clark; Kurt G. Harris; Y. E. Kim; Kary R. Schulte (Annals of Biomedical Engineering, 1989)